TUMBUHKAN TANAMAN TANPA TANAH INOVASI PERTANIAN HIDROPONIK DI KWT NUSA INDAH KELURAHAN CIBODAS KOTA TANGERANG - Latuconsina, Hudaya; Lesmana, Sri Jaya; Djamaludin, Djamaludin; Fahmi, Rizal (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Hydroponics is a method of planting plants that uses water as a planting medium without using soil. Kale hydroponics is one example of the application of hydroponic methods to vegetable plants that are popular in Indonesia. The purpose of this activity is to examine the advantages and challenges of kale hydroponics, as well as provide recommendations for mothers at KWT Nusa Indah. The results of the activity show that kale hydroponics has several advantages, including: (1) it can save land, water, and fertilizer; (2) it can produce high-quality kale with short harvest time; (3) can reduce the risk of soil contamination and plant diseases; (4) can increase the added value and income of farmers. However, kale hydroponics also has several challenges, including: (1) requires a considerable initial capital; (2) requires special knowledge and skills in the management of hydroponic systems; (3) requires intensive and routine maintenance; (4) are susceptible to electrical disturbances and climate change. Therefore, this activity recommends several steps to overcome these challenges, including: (1) providing capital assistance, equipment, and materials from the government or related institutions; (2) organizing training and guidance for farmers on hydroponic techniques; (3) using alternative energy sources such as solar panels or generators; (4) Using an automatic control system to regulate the pH, nutrients, and temperature of the water. This activity was carried out by Group 4 Students of the UNIS Tangerang Community Work Lecture (KKK) in Cibodas Village, precisely KWT Nusa Indah Rw 04 is expected to contribute to women at KWT Nusa Indah. Kale hydroponics as a modern planting method that is environmentally friendly and efficient